Evaluation of pyraclostrobin as a management tool of Groundnut ringspot virus in peanut crop - Michelotto, Marcos Doniseti; de Cássia Pereira-Carvalho, Rita; de Nazaré Almeida dos Reis, Luciane; Boiteux, Leonardo Silva; Carrega, Willians César [UNESP]; Lamana, Luis Eduardo Prado; de Godoy, Ignácio José (Springer Nature, 2020)
Yield losses due to Groundnut ringspot virus – GRSV (genus Orthotospovirus) infection have been observed across major peanut (Arachis hypogaea L.) growing areas in Brazil. However, effective management systems capable of minimizing GRSV damage are not yet available. The aim of the present study was to verify the effectiveness of the pyraclostrobin (a strobilurin fungicide reported as a potential activator of natural, large–spectrum plant defense mechanisms) in the management of GRSV in peanuts. Two independent field experiments were carried out in commercial peanut areas with a natural occurrence of GRSV. A completely randomized block design was used with a 5 × 2 factorial scheme, including four replicates, five peanut cultivars (‘Runner IAC 886’, ‘IAC OL4’, ‘IAC 503’, ‘IAC 505’, and ‘Granoleico’) and two treatments (with and without pyraclostrobin application). At 80 and 100 days after sowing, visual disease severity scores and the number of infected plants were evaluated, followed by virus quantification in the leaf tissues and yield. The cultivars ‘Granoleico’ and ‘IAC 503’ displayed the highest levels of GRSV susceptibility. Pyraclostrobin was found to be effective in reducing the number of GRSV–infected plants, as well as in attenuating disease severity. In addition, pyraclostrobin was able to promote significant yield increase. Even though the mechanism(s) of pyraclostrobin action against GRSV remain elusive, this fungicide can be regarded as a potential component for viral disease management programs in peanuts.
Keywords: Arachis hypogaea; Damages; Fungicide; Losses; Orthotospovirus